Compliance-To-Competitive Advantage Framework: A Digital Transformation Strategy for Hospitals Based on Regulatory Compliance, Operational Efficiency, and Service Value - Purwadhi; Yani Restiani Widjaja; Tan Fransisca Dian; Elsa Fitriani (Jurnal Indonesia Sosial Sains, 2026)
Hospital digital transformation is often narrowly understood as an administrative obligation to comply with regulations, particularly the implementation of Electronic Medical Records and the integration of national health data. However, when managed as an organizational strategy, digital transformation can be a crucial instrument for improving operational efficiency, strengthening service quality, and building a hospital's competitive advantage. This article aims to develop a conceptual framework for hospital digital transformation based on regulations, operational efficiency, and service value through a narrative literature review approach. The literature was analyzed thematically by combining the perspectives of strategic management, digital transformation, electronic medical records, Indonesian health regulations, the resource-based view, and dynamic capabilities. The study results indicate that hospital digital transformation should not stop at regulatory compliance but should be directed at business process integration, data utilization for decision-making, strengthening the organization's digital capabilities, and creating value for patients and stakeholders. This article proposes the Compliance-to-Competitive Advantage Framework, a step-by-step model that links digital regulatory pressures with the development of digital capabilities, operational efficiency, service value, and competitive advantage. This framework can serve as a practical guide for hospital management in designing a digital transformation that not only fulfills obligations but also generates strategic value.